Advance in Iron Metabolism, Oxidative Stress and Cellular Dysfunction in Experimental and Human Kidney Diseases - Tiancheng Xie; Li Yao; Xiaogang Li (MDPI AG, 2024)
Kidney diseases pose a significant global health issue, frequently resulting in the gradual decline of renal function and eventually leading to end-stage renal failure. Abnormal iron metabolism and oxidative stress-mediated cellular dysfunction facilitates the advancement of kidney diseases. Iron homeostasis is strictly regulated in the body, and disturbance in this regulatory system results in abnormal iron accumulation or deficiency, both of which are associated with the pathogenesis of kidney diseases. Iron overload promotes the production of reactive oxygen species (ROS) through the Fenton reaction, resulting in oxidative damage to cellular molecules and impaired cellular function. Increased oxidative stress can also influence iron metabolism through upregulation of iron regulatory proteins and altering the expression and activity of key iron transport and storage proteins. This creates a harmful cycle in which abnormal iron metabolism and oxidative stress perpetuate each other, ultimately contributing to the advancement of kidney diseases. The crosstalk of iron metabolism and oxidative stress involves multiple signaling pathways, such as hypoxia-inducible factor (HIF) and nuclear factor erythroid 2-related factor 2 (Nrf2) pathways. This review delves into the functions and mechanisms of iron metabolism and oxidative stress, along with the intricate relationship between these two factors in the context of kidney diseases. Understanding the underlying mechanisms should help to identify potential therapeutic targets and develop novel and effective therapeutic strategies to combat the burden of kidney diseases.